1992
DOI: 10.1007/bf01000158
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic receptors coupled to adenylate cyclase in human cerebromicrovascular endothelium

Abstract: Cultured endothelium derived from three microvascular fractions of human brain was used to characterize adrenergic receptors coupled to adenylate cyclase activity. Catecholamines (norepinephrine, epinephrine) and their analogs (isoproterenol, phenylephrine, 6-fluoronorepinephrine) dose-dependently stimulated endothelial production of cAMP. Antagonists for beta 1 and beta 2 receptors (propranolol, atenolol, and butoxamine) and for alpha 1-receptors (prazosin) dose-dependently blocked cAMP formation induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Adrenaline receptor is a well-known G s proteincoupled receptor, thus the activation of adrenaline receptor results in increased cAMP concentration in endothelial cells [26]. Although several studies have investigated the role of cAMP in the modulation of adhesion molecule abundance, the findings obtained so far remain controversial.…”
Section: Discussionmentioning
confidence: 84%
“…Adrenaline receptor is a well-known G s proteincoupled receptor, thus the activation of adrenaline receptor results in increased cAMP concentration in endothelial cells [26]. Although several studies have investigated the role of cAMP in the modulation of adhesion molecule abundance, the findings obtained so far remain controversial.…”
Section: Discussionmentioning
confidence: 84%
“…The S1P response is modulated by S1P 1 receptors that are coupled to G i (36,37), whereas ␤ 3 -adrenergic receptors are coupled to G s pathways (38). It thus appears that the small G protein Rac1 may be a downstream effector of both G s -as well as G i -coupled receptors.…”
mentioning
confidence: 99%
“…Our previous studies on the cerebral cortex (Lukaszyk et al 1984), subfornical organ (Wrzolkowa and Lukaszyk 1986) and amygdaloid body (Lukaszyk and Wrzotkowa 1987), together with the observations of other investigators (Raichle et al 1975;Rennels and Nelson 1975;Itakura et al 1977;Swanson et al 1977;Edvinsson et al 1980;Madison et al 1981;Betz and Goldstein 1984;Lou et al 1987;Palmer 1986;Harik 1988;Bacic et al 1992), suggested the existence of a functional connection between axon terminals and capillary vessel walls in the CNS. The results of the present study further support this hypothesis by showing ultrastructural differences between the populations of PAT and DAT in the Cat amygdala.…”
Section: Discussionmentioning
confidence: 82%